ANALISIS SEKTOR UNGGULAN DAN PENYERAPAN TENAGAKERJA DI PROVINSI SULAWESI TENGGARA - Darman, Darman; Nur Afiat, Muhammad (JURNAL EKONOMI UHO, 2016)
The agriculture sector contributed in  higer  proportion on gross domestic product of   South East Sulawesi, but in employment side, there are decreasing trend of agricultural for some period.  This study  aims to find out leading sectors in Southeast Sulawesi Province  in term output and employment. Data analysis with Location Quatient (LQ) approach for 2004-2013 periode was collected from South East Statistics  Bureau. The results show that the leading or basis sector  South East Sulawesi are agriculture, transportation and services is  indicated by LQ>1.  The agriculture is  basis sector also in term labor absorption in overall period of analysis.